2008
DOI: 10.1523/jneurosci.2918-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Signaling Does Not Stimulate Subventricular Zone Neurogenesis in Adult Mice and Rats

Abstract: In rodents, the adult subventricular zone (SVZ) generates neuroblasts which migrate to the olfactory bulb (OB) and differentiate into interneurons. Recent work suggests that the neurotrophin Brain-Derived Neurotrophic Factor (BDNF) can enhance adult SVZ neurogenesis, but the mechanism by which it acts is unknown. Here, we analyzed the role of BDNF and its receptor TrkB in adult SVZ neurogenesis. We found that TrkB is the most prominent neurotrophin receptor in the mouse SVZ, but only the truncated, kinasenegat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
111
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 94 publications
(137 reference statements)
14
111
1
3
Order By: Relevance
“…Moreover, in vivo, the compound increases formation of new BrdU1/PSA-NCAM1 cells, and ultimately increases numbers of mature neurons in both injured and uninjured animals. p75 NTR has been implicated as a direct regulator of neurogenesis [12,66] and studies with mice expressing a mutant p75 NTR unable to bind neurotrophins suggest that p75 NTR -expressing precursors are a principal source of new neurons in the dentate [13,15,67]. The increase in BrdU1/PSA-NCAM1 cell numbers both in vitro and in vivo is roughly proportionate to LM11A-31-induced proliferation, and the effects of this appear to carry through to several months following injury, resulting in recovery of numbers of BrdU1/NeuN1 cells compared to vehicle-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vivo, the compound increases formation of new BrdU1/PSA-NCAM1 cells, and ultimately increases numbers of mature neurons in both injured and uninjured animals. p75 NTR has been implicated as a direct regulator of neurogenesis [12,66] and studies with mice expressing a mutant p75 NTR unable to bind neurotrophins suggest that p75 NTR -expressing precursors are a principal source of new neurons in the dentate [13,15,67]. The increase in BrdU1/PSA-NCAM1 cell numbers both in vitro and in vivo is roughly proportionate to LM11A-31-induced proliferation, and the effects of this appear to carry through to several months following injury, resulting in recovery of numbers of BrdU1/NeuN1 cells compared to vehicle-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…These neurons express specific cell surface markers spatiotemporally depending on their maturity and microenvironment (8). The pluripotent neurons from the SVZ and SGZ seem to play different roles and to be regulated by distinct mechanisms (9). By investigating the factors modulating adult neurogenesis, neuronal activity, environmental factors, and psychotropic drugs have been shown to dynamically regulate adult neurogenesis (10).…”
Section: The Generation Of New Neurons In the Mammalian Brainmentioning
confidence: 99%
“…BDNF and its receptors of high and low affinity, TrkB and p75 NTR , respectively, are expressed all over the SVZ-RMS in a mutually exclusive pattern; with higher expression of BDNF and TrkB in the RMS when compared to the SVZ (Bath et al, 2008;Chiaramello et al, 2007;Galvão et al, 2008;Gascon et al, 2007;Giuliani et al, 2004;Maisonpierre et al, 1990;Snapyan et al, 2009;Young et al, 2007). In the adult RMS, BDNF mRNA expression was identified in endothelial cells of blood vessels, and absent in astrocytes as well as neuroblasts (Snapyan et al 2009), whereas TrkB was found predominantly in astrocytes (Snapyan et al 2009).…”
Section: Bdnf: a Multitask Moleculementioning
confidence: 99%
“…In the adult RMS, BDNF mRNA expression was identified in endothelial cells of blood vessels, and absent in astrocytes as well as neuroblasts (Snapyan et al 2009), whereas TrkB was found predominantly in astrocytes (Snapyan et al 2009). Conversely, active TrkB (phosphorylated form) as well as the low affinity receptor p75 NTR have been observed in migrating neuroblasts (Bath et al, 2008, Galvão et al, 2008Snapyan et al, 2009). P75 NTR is also present in a small subset of GFAPimmunopositive cells and transit amplifying cells (C-cells) in the RMS (Bath et al, 2008, Galvão et al, 2008Snapyan et al, 2009).…”
Section: Bdnf: a Multitask Moleculementioning
confidence: 99%
See 1 more Smart Citation